2023
DOI: 10.3390/jcdd10090388
|View full text |Cite
|
Sign up to set email alerts
|

Vericiguat: The Fifth Harmony of Heart Failure with Reduced Ejection Fraction

Luigi Falco,
Benedetta Brescia,
Dario Catapano
et al.

Abstract: Heart failure with reduced ejection fraction is a chronic and progressive syndrome that continues to be a substantial financial burden for health systems in Western countries. Despite remarkable advances in pharmacologic and device-based therapy over the last few years, patients with heart failure with reduced ejection fraction have a high residual risk of adverse outcomes, even when treated with optimal guideline-directed medical therapy and in a clinically stable state. Worsening heart failure episodes repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 77 publications
0
1
0
Order By: Relevance
“…Furthermore, the drug has also been associated with improving the overall quality of life, which was also observed in our patient [6,7]. Subsequent studies to the VICTORIA trial have demonstrated that patients with an NT-proBNP level below 8000 pg/ml experience a reduction in cardiovascular mortality or initial hospitalization for heart failure, suggesting that the treatment is most beneficial for patients with less advanced HFrEF [9,10].…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, the drug has also been associated with improving the overall quality of life, which was also observed in our patient [6,7]. Subsequent studies to the VICTORIA trial have demonstrated that patients with an NT-proBNP level below 8000 pg/ml experience a reduction in cardiovascular mortality or initial hospitalization for heart failure, suggesting that the treatment is most beneficial for patients with less advanced HFrEF [9,10].…”
Section: Discussionsupporting
confidence: 72%
“…Subsequently, triple neurohormonal blockade and then quadruple therapy have become the standard of care (SoC). To date, several different pathways are successfully targeted with novel drugs [ 1 , 2 ]. Thus, HF specialists went from an era in which disease-modifying therapies were lacking to a new era, where they needed to tailor pharmacologic treatment according to patients’ phenotype.…”
Section: Chronic Heart Failure: Focus On Pharmacological Therapymentioning
confidence: 99%
“…Additionally, based on clinical profiles, [4] further medications are recommended to improve patients' QoL and functional capacity and reduce hospitalizations, with Vericiguat being the first to enhance an endogenous pathway rather than inhibit it. [5] Despite these remarkable advances, the registry data are not reassuring. First, HF's prevalence is rising worldwide, and not only because of population aging.…”
Section: Introductionmentioning
confidence: 99%